2020
DOI: 10.1177/1941738120922163
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Sports Health: Authorship Characteristics and Levels of Evidence

Abstract: Context: Sports Health: A Multidisciplinary Approach, now 10 years into production, has been ranked a top-25 journal in sport sciences and has tripled its impact throughout its existence. Objective: To evaluate authorship trends and levels of evidence (LOE) of articles published in Sports Health from 2009 to 2018. The secondary aim was to analyze funding sources and internationalization throughout the jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…They found that the percentage increase of female first authorship was 64% (p < 0.0001) with 12.4% (n = 211) of first authors being females and 87.6% (n = 1,486) being males over that period. A similar study by Judy et al 19 systematically reviewed 654 articles published in Sports Health from 2009 to 2018. This study showed a 12% increase (p < 0.05) in female authorship over that period (Table VIII).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the percentage increase of female first authorship was 64% (p < 0.0001) with 12.4% (n = 211) of first authors being females and 87.6% (n = 1,486) being males over that period. A similar study by Judy et al 19 systematically reviewed 654 articles published in Sports Health from 2009 to 2018. This study showed a 12% increase (p < 0.05) in female authorship over that period (Table VIII).…”
Section: Resultsmentioning
confidence: 99%
“…An improved understanding of gender and URM trends within sports medicine research involvement may in part explain promotion trends, as authorship is frequently used as a quantitative metric of professional influence and accomplishments 35,36 . The data from all articles analyzed demonstrated statistically significant increases in the proportion of female authorship over time in AJSM, Arthroscopy, and Sports Health regarding overall, first, and senior authorship [17][18][19][20] . Although these data are encouraging, it is difficult to extract conclusions, as the number of female authors without an MD or PhD was 41.1% (n 5 2,048) compared with males 15.8% (n 5 3,954) 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation